EVOLUSI MODEL COOPERATIVE LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: ANALISIS BIBLIOMETRIK PUBLIKASI SCOPUS (2015-2025) - Najwan, Rifdah; shobah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the evolution and research trends of cooperative learning in Islamic Religious Education through a bibliometric approach. A descriptive quantitative design was employed using bibliometric analysis to map publication patterns, research trends, and thematic development in this field. Data were retrieved from the Scopus database using the keywords “cooperative learning,” “Islamic education,” “Islamic religious education,” and “Pendidikan Agama Islam,” covering publications from 2015 to 2025. The initial search yielded 956 documents, which were subsequently screened based on predefined inclusion and exclusion criteria, resulting in 148 relevant articles for analysis. The data were analyzed descriptively and visually using VOSviewer to identify publication trends, influential journals, authorship collaboration, and keyword co-occurrence networks. The results indicate an increasing trend of publications related to cooperative learning in Islamic Religious Education, with dominant themes focusing on student engagement, learning outcomes, and collaborative instructional strategies. This study provides a comprehensive overview of the intellectual structure and research directions in this field and offers a reference for future research development.